Experimental study on a multi-evaporator refrigeration system with variable area ratio ejector - Li, Cui (2017)
This paper describes an experimental study on a multi-evaporator refrigeration system (MERS) with conventional pressure regulating valve (PRV) and variable area ratio ejector. Some key performance indicators such as cooling capacity, power consumption and ejector entrainment ratio were evaluated by switching operating modes, adjusting superheat and tuning ejector spindle and so on. The results indicated that: (1) the energy efficiency of the MERS can be improved by up to 12% by replacing the conventional pressure regulating valve with the variable area ratio ejector, (2) sufficient superheat or superheat degree greater than 2 °C is conducive to high entrainment performance of the ejector, large cooling capacity of the low-temperature evaporator and low power consumption of the system, and (3) the effect of nozzle spindle position on the performance of the system is evident.